Dietary preferences affect the gut microbiota of three snake species (Squamata: Colubridae) - Zhu, Guangxiang; Song, Huina; Duan, Mingwen; Wang, Ji; Luo, Jingxue; Yang, Shijun; Wu, Fei; Jiang, Jiuyan; Chen, Ji; Tang, Wenjiao (Frontiers in Microbiology, 2025)
IntroductionThe gut microbiota is an emerging frontier in animal research, and researchers are increasingly transparent about its importance to animal health. Reptiles, particularly snakes, have not received the same attention given to other vertebrates, and the composition of their wild gut microbiome remains understudied.MethodsIn this study, the HiSeq high-throughput sequencing platform was used to sequence and analyze the 16S rRNA V4 region of the gut microbiota of three species (Gonyosoma coeruleum, Rhabdophis pentasupralabralis, Rhabdophis tigrinus).ResultsThis study investigated alpha diversity analysis and showed that the gut microbiota richness of RP was significantly higher than that of the other two snakes. The dominant genus of Gonyosoma coeruleum (GC) and Rhabdophis tigrinus (RT) is Cetobacterium, while Enterobacteriaceae; g_uncultured is the dominant genus of Rhabdophis pentasupralabralis (RP). Tree clustering based on Bray-Curtis distances and Jaccard similarity coefficients indicated that the gut microbiota composition of RP and RT was more similar. The unique diet of RP promotes a diverse, competitive gut microbiota, while GC and RT displayed more stable networks linked to shared dietary habits. The functional heat map showed that the predicted functions of the gut microbes of the three snake species were different. These findings suggest that dietary preferences exert a stronger influence on gut microbial composition and function than host genetic background, and distantly related species with similar diets exhibit convergent gut microbiota characteristics.